Design Improvement of A Prototype Energy-Efficient Vehicle Body - Putra, Haznam; Mulyadi, Ismet Hari (JURNAL CRANKSHAFT, 2024)
In order to achieve an energy-efficient vehicle, many aspects had to be considered, including the weight of the vehicle's body. The weight of the vehicle's body depends on its design and materials. As part of the energy-efficient initiatives, the design of the energy-efficient car developed by a Mechanical Engineering Team of Universitas Andalas needs to be redefined to improve its performance due to its active participation in national competition. Autodesk Inventor software's capability supported a reverse engineering strategy to enhance the car body design. Meanwhile, the appropriate car body material was selected using the Analytic Hierarchy Process (AHP). Furthermore, the improved car body design was evaluated using an academic version of ANSYS R1 and Fluent software. A weight reduction of 8 Kg is gained due to improving the new car body design and with the achievable thickness of 3.4 mm. Accordingly, it could minimize the Coefficient Drag (CD) of the new car body design to 0.066275. This result indicates a further improvement of the new energy-efficient car body design that would accelerate the car's performance and gain better results in the next national energy-efficient vehicle competition.